PENERAPAN KEGIATAN ECOPRINT DENGAN TEKNIK POUNDING DALAM MENINGKATKAN KREATIVITAS ANAK KELOMPOK B DI KB NURUL ITTIHAD - Milawati; M.A Muazar Habibi; Dwi Amalina Wahab, Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low creativity of group B children at KB Nurul Ittihad, which is shown through the children's lack of ability to develop ideas, express imagination, produce original work, and the tendency to imitate examples given by teachers. This condition is caused by learning activities that are still monotonous and do not provide opportunities for children to explore freely. Therefore, innovative and fun learning activities are needed, one of which is through ecoprint activities with the pounding technique that utilizes natural materials as a medium for work. This study aims to determine the application of ecoprint activities with the pounding technique in increasing the creativity of group B children at KB Nurul Ittihad. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which is carried out in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects were 12 group B children at KB Nurul Ittihad. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used quantitative and qualitative descriptive analysis. The results of the study indicate that the application of ecoprint activities with the pounding technique can gradually increase children's creativity. The percentage of children's creativity increased from 16.67% in the pre-cycle stage to 33.34% in cycle I, then increased significantly to 91.67% in cycle II. In addition to increasing creativity, this activity was also able to increase children's activeness, self-confidence, ability to explore, and enthusiasm during the learning process. Thus, ecoprint activities using the pounding technique have proven effective as an innovative, environmentally-based learning alternative to enhance creativity in early childhood.